Dehydroepiandrosterone (DHEA) Sensitizes Irinotecan to Suppress Head and Neck Cancer Stem-Like Cells by Downregulation of WNT Signaling - Li, Li-Jie; Li, Chien-Hsiu; Chang, Peter Mu-Hsin; Lai, Tsung-Ching; Yong, Chen-Yin; Feng, Sheng-Wei; Hsiao, Michael; Chang, Wei-Min; Huang, Chi-Ying F. (Frontiers in Oncology, 2022)
Purpose: Current treatment options for head and neck squamous cell carcinoma (HNSCC) are limited, especially for cases with cancer stem cell-induced chemoresistance and recurrence. The WNT signaling pathway contributes to maintenance of stemness via translocation of β-catenin into the nucleus, and represents a promising druggable target in HNSCC. Dehydroepiandrosterone (DHEA), a steroid hormone, has potential as an anticancer drug. However, the potential anticancer mechanisms of DHEA including inhibition of stemness, and its therapeutic applications in HNSCC remain unclear. Methods: Firstly, SRB assay and sphere formation assay were used to examine cellular viability and cancer stem cell-like phenotype, respectively. The expressions of stemness related factors were measured by RT-qPCR and western blotting. The luciferase reporter assay was applied to evaluate transcriptional potential of stemness related pathways. The alternations of WNT signaling pathway were measured by nuclear translocation of β-catenin, RT-qPCR and western blotting. Furthermore, to investigate the effect of drugs in vivo, both HNSCC orthotopic and subcutaneous xenograft mouse models were applied. Results: We found that DHEA reduced HNSCC cell viability, suppressed sphere formation, and inhibited the expression of cancer-stemness markers, such as BMI-1 and Nestin. Moreover, DHEA repressed the transcriptional activity of stemness-related pathways. In the WNT pathway, DHEA reduced the nuclear translocation of the active form of β-catenin and reduced the protein expression of the downstream targets, CCND1 and CD44. Furthermore, when combined with the chemotherapeutic drug, irinotecan (IRN), DHEA enhanced the sensitivity of HNSCC cells to IRN as revealed by reduced cell viability, sphere formation, expression of stemness markers, and activation of the WNT pathway. Additionally, this combination reduced in vivo tumor growth in both orthotopic and subcutaneous xenograft mouse models. Conclusion: These findings indicate that DHEA has anti-stemness potential in HNSCC and serves as a promising anticancer agent. The combination of DHEA and IRN may provide a potential therapeutic strategy for patients with advanced HNSCC.